Infrared Drying Trends Applied to Fruit - Zartha Sossa, Jhon Wilder; Orozco, Gina Lía; García Murillo, Liz Mercedes; Peña Osorio, Miguel; Sánchez Suarez, Nevardo (Frontiers in Sustainable Food Systems, 2021)
Aims: This article seeks to identify the main products to which drying is applied, mainly by infrared, as well as the mathematical models used to evaluate a product. Background: The drying of agro-industrial products is a very important unitary operation to avoid post-harvest losses. Objective: This article looks to respond to the following questions: Which raw materials are subjected to far-infrared drying? What are the mathematical models used in the application of far-infrared? Method: To identify the most focused articles on the topic, we worked with the search equation “TITLE-ABS-KEY (‘infrared drying’) AND fruits AND [LIMIT-TO (SUBJAREA, ‘AGRI’) OR LIMIT-TO (SUBJAREA, ‘ENGI’)],” which was run in the Scopus database for scientific articles. Result: After knowing the different technologies, more than 23 applications in agro-industrial products were identified. In these applications, it is observed how quality is one of the most important factors in the preservation of dehydrated products; far-infrared drying helps retain sensory quality in products such as sweet potatoes, grapes, Cordyceps militaris, and mangoes. Conclusion: A common factor that could be found from the articles and patents was the application of this infrared drying technique in fruits and vegetables with high water content, such as kiwi, chives, and mushroom varieties. These articles and patents based their studies on optimizing the technique by varying drying times, temperatures, and pressures, even sometimes combining different drying techniques—all to preserve the organoleptic characteristics of the product, avoiding damage to thermolabile compounds and obtaining a dry food of very good quality, performance, and characteristics.